Image classification and region analysis using statistical approach - Ying, Cao. (2008)
One of the difficult problems in the indexing and retrieving of image database is to find an effective and robust method to classify images. The classification, however depends on the features obtained from image. In this thesis, we study two approaches using color and texture feature for classification of color image and texture image, respectively.